ANALISIS PENGGUNAAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING GUNA MENGATASI KURANGNYA KETERAMPILAN BERPENDAPAT DI SD NEGERI SERANG 21 - Alma Maulida (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2022)
In every learning process there are problems, both from students, teachers, or from existing facilities and infrastructure. This study aims to describe the use of problem-based learning models to overcome the lack of opinion skills in students in grade 4. This study used a descriptive qualitative method and was conducted at SD Negeri Serang 21. Data collection techniques in this study used observation, application of lesson plans, and documentation. The results of this study indicate an increase in students opinions during the learning process using the problem-based learning model.